2022
DOI: 10.3390/jcm11133597
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Analysis of the Therapeutic Management and Disease Burden in Chronic Myeloid Leukemia Patients with Later Lines in Italy

Abstract: Real world data are becoming a crucial tool to understand how cancer is treated in routine daily practice. This real-world analysis aims to describe the characteristics of patients with CML in 2nd or ≥3rd tyrosine kinase inhibitors (TKI) lines of therapy, to evaluate their treatment sequence and utilization in settings of Italian clinical practice in Italy. A retrospective analysis was performed using an administrative databases covering around 15.3 million cases. All adult patients prescribed with TKI as 2nd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…1 b): 38 (26.4%) received imatinib, 32 (22.2%) ponatinib, 27 (18.8%) nilotinib, 24 (16.7%) bosutinib, and 23 (16.0%) dasatinib. Characteristics of patients were described elsewhere [ 13 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 b): 38 (26.4%) received imatinib, 32 (22.2%) ponatinib, 27 (18.8%) nilotinib, 24 (16.7%) bosutinib, and 23 (16.0%) dasatinib. Characteristics of patients were described elsewhere [ 13 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Notably the most used TKI in the 3rd L cohort was imatinib. The sequence pattern of this subset of patients [ 13 ] shows that patients treated with first line imatinib, after receiving a different TKI in 2nd line, switched back to imatinib. Consistently, other real-world studies on patients with CML, have reported this trend, showing that a sizeable portion of patients in their later lines, at some point, switch back to imatinib [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 Further, a substantial proportion (30–50%) requires multiple lines of treatment before adequate disease management, 12–16 and this may be associated with a greater burden on aspects of daily life (e.g., psychosocial, physical, financial). 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
“…11 Further, a substantial proportion (30-50%) requires multiple lines of treatment before adequate disease management, [12][13][14][15][16] and this may be associated with a greater burden on aspects of daily life (e.g., psychosocial, physical, financial). 17,18 Impacts on well-being result from any cancer diagnosis, and labelling a cancer as "good" is not helpful to individuals with the diagnosis. 19,20 While presumably used to promote feelings of reassurance at diagnosis, as time progresses, patients may feel misunderstood or isolated, and could feel that their health care provider (HCP) does not take their diagnosis seriously, leading to hesitation to share concerns with HCPs.…”
Section: Introductionmentioning
confidence: 99%